Exploring the role of Portuguese brands' actions on social media on consumer engagement - Pinto, Luísa Maria dos Santos Jorge Teixeira (2018)
With the progressive evolution of technology, digital communications and social media quickly turned into an indispensable practice of people's daily lives. At the same time, from a consumer point of view, individuals crave more than just transactional exchanges, they want to bond, connect with brands and engage in two-way communications. As a result, marketers saw a real opportunity in social media, as an instrument to nurture relationships, interact with consumers and increase engagement. However, due to the lack of literature concerning the impact of brand-owned communities on users' behaviour, this study aims to comprehend the role of firm-generated content on consumer engagement, investigating for that purpose, three Portuguese brand fan pages on Facebook and Instagram. In order to do so, two complementary topics connected to the subject were also investigated online relationship cultivation strategies, and the combination of traditional and digital communications- to achieve a more realistic perspective regarding marketing communications in the digital world. Results showed that brands implement interactivity and involvement strategies on Facebook and Instagram as a way to connect and boost consumer's participation. Additionally, fans respond better to photo-based posts and most commonly react to those posts through "likes". Finally, regarding engagement rate, Instagram scored higher than Facebook.